Classroom Management: A Prerequisite to Pre-Schoolers Motivation and Affection Toward Learning and School in Edo South Senatorial Districts - Iyamu, I. F.; Kennedy, Imasuen (European Journal of Applied Sciences, 2021)
Early education of children in Nigeria has been of great concern to both the parents, educators and other stake holders in education. This has led to a high investment in the educational sector, bus less progress is made in the pre-primary level. A lot of questions have risen as to why this low progress is been made. Some attributed this low progress to the issue of classroom management, teacher motivation and many more. This study therefore examined classroom management as a prerequisite to pre-schoolers motivation and affection toward learning and school in Edo south senatorial districts. The study was a descriptive design and four research questions were raised to guide the study. The target population comprised classroom teachers in both private and public pre-primary schools in Edo South senatorial district of Edo State. The sample for this study was five hundred (500) teachers, who were drawn from private and public pre-primary schools in the senatorial district. The research instrument used for this study was a questionnaire designed by the researchers; it was a four-Likert scale. It had two sections; Section A consists of the demographic data of the respondents while Section B contained the questions that elicited responses from the respondents with response options like, Strongly Agree, Agree, Strongly Disagree and Disagree. The face and content validity of the instrument was determined by three experts in the field. Cronbach alpha method was used to ascertain the reliability of the instrument. It gave an alpha value of 0.89 which indicated that the instrument was reliable. Data gathered through the questionnaire were analysed using mean and standard deviation, chi-square and multiple regressions. A criterion mean of 2.50 was used for the acceptance of the items while an interpretative norm of 7.50 which was the product of the criterion mean and the number of items in each cluster was used to ascertain the extent of teachers’ classroom management and motivation on children’s affection for school. The findings proved that classroom management affects children’s motivation and affection for learning and school, however, teacher motivation was not significant. It was therefore concluded that classroom management is a significant factor in facilitating pupil motivation and affection to learning and school. The study therefore recommended that School teachers should be made to go for periodical in-service training on classroom management courses and Education stakeholder should invest more in learning environment and make it more attractive to learners by providing all necessary learning facilities.